USDA-DHIA Sire Summaries-AI Advantage - Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
USDA-DHIA Sire Summaries are published semiannually and provide the dairy industry with an accurate evaluation of the transmitting ability of bulls for milk and milk components. Genetic potential is established at the time of conception. Therefore, current service sires represent the primary means of improving the genetic base of the future herd. Based upon first evaluation of daughters of AI and non-AI bulls, the data clearly indicate the genetic superiority of bulls selected by the AI industry. Dairy producers are strongly urged to select service sires from the Active AI bull listings.
Keywords: Dairy; Artificial Insemination (AI); Genetics; Milk production